2011
DOI: 10.5194/hess-15-2717-2011
|View full text |Cite
|
Sign up to set email alerts
|

Discharge estimation in a backwater affected meandering river

Abstract: Abstract. Variable effects of backwaters complicate the development of rating curves at hydrometric measurement stations. In areas influenced by backwater, single-parameter rating curve techniques are often inapplicable. To overcome this, several authors have advocated the use of an additional downstream level gauge to estimate the longitudinal surface level gradient, but this is cumbersome in a lowland meandering river with considerable transverse surface level gradients. Recent developments allow river flow … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 27 publications
(45 reference statements)
0
48
0
4
Order By: Relevance
“…The other most classical example is the hysteretic relation between water level and discharge during backwater events (Herschy, 2009;Hidayat et al, 2011). As has been well documented, single-parameter rating curves developed for particular hydrometric stations fail to reflect the real discharge under unsteady flow occurring during backwaters or flood propagation waves (Hidayat et al, 2011;Mrokowska et al, 2014;Petersen-Overleir, 2006;Rowiński et al, 2000). To compare, the studies of Moog and Whiting (1998) have shown the hysteresis between river discharge and bed load transport, whereas Williams (1989) reported hysteresis between discharge and sediment concentration rates during flood events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other most classical example is the hysteretic relation between water level and discharge during backwater events (Herschy, 2009;Hidayat et al, 2011). As has been well documented, single-parameter rating curves developed for particular hydrometric stations fail to reflect the real discharge under unsteady flow occurring during backwaters or flood propagation waves (Hidayat et al, 2011;Mrokowska et al, 2014;Petersen-Overleir, 2006;Rowiński et al, 2000). To compare, the studies of Moog and Whiting (1998) have shown the hysteresis between river discharge and bed load transport, whereas Williams (1989) reported hysteresis between discharge and sediment concentration rates during flood events.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was applied in conceptual models such as linear reservoirs (O'Kane, 2005). The other most classical example is the hysteretic relation between water level and discharge during backwater events (Herschy, 2009;Hidayat et al, 2011). As has been well documented, single-parameter rating curves developed for particular hydrometric stations fail to reflect the real discharge under unsteady flow occurring during backwaters or flood propagation waves (Hidayat et al, 2011;Mrokowska et al, 2014;Petersen-Overleir, 2006;Rowiński et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…They have a function as a buffer by storing water during the high flow conditions, and releasing it during low flows. Lake filling and emptying mechanisms play a role to shave water level peaks downstream of the Mahakam lakes area (Hidayat et al, 2011b). The MMA is also surrounded by peatland, as part of the Kutai lowland spreading over an area of 35 km NW-SE by 130 km SW-NE, with elevations of around sea level in the Mahakam River to ca.…”
Section: Study Areamentioning
confidence: 99%
“…However, if most precipitation would be concentrated further upstream in the Meuse basin, the difference in 15 travel time would merely increase by about two days (Figure 12). Two days extra travel time would still result in simultaneous cause backwater effects apparent as hysteresis in a rating curve cannot be readily accounted for (Figure 11) (Hidayat et al, 2011(Hidayat et al, , 2016. During the highest discharge waves, backwater variation shows to be most severe.…”
mentioning
confidence: 99%